Peran Gerakan Hak Sipil dalam Membentuk Masyarakat Amerika: Analisis Sejarah dan Dampaknya, 1950-1960 - Sinurat, Gabriel Joey Febriand; Lubis, Salsabila; Sibarani, Tesa Romanti; Wisabla, Nelman; Aruan, Friska Fransiska; Charisma, Ilmiyatul Fitri; Manurung, Nadya Katerina; Pakpahan, Gabriel (Polyscopia, 2024)
This study analyzes the important role of the Civil Rights Movement in shaping United States society through a historical approach and its impact. It explores the movement's long history, from its 19th-century roots to the monumental struggles of the 20th century, revealing how it emerged in response to rampant social, racial, and political injustice. By examining key figures, strategies, and important events, this study traces the evolution of the movement from the anti-slavery era to the Civil Rights Movement of the 1950s and 1960s. Additionally, it examines the movement's impact on American society, highlighting significant transformations in law, policy, and societal perceptions of civil rights and equality. The study also documents the movement's legacy in driving systemic change and shaping views on inclusion, justice, and diversity. In conclusion, the Civil Rights Movement has played a crucial role in shaping modern American society by laying the foundation for progress toward equality, justice, and human rights, with its legacy continuing to influence ongoing struggles for a more just and inclusive society.